Neem relative growth under supplementary irrigation with saline waters and biofertilizer - Mesquita, Francisco de Oliveira; Cavalcante, Lourival Ferreira; Oliveira Filho, Francisco Xavier de; Rodrigues, Rummenigge de Macêdo; Campos, Vinícius Batista; Souza, Jânio Kleiber Camelo de (Comunicata Scientiae, 2019)
An experiment was performed, during the period from January to July, 2016, in a screened environment of the Department of Soils and Rural Engineering of the Agrarian Sciences Center, Federal University of Paraiba (UFPB), Areia, Paraiba, Brazil, with the purpose of evaluating the effects of supplementary irrigation with saline waters over the relative growth of Indian neem seedlings, in soil with bovine biofertilizer. The substrate used was a dystrophic Yellow-Red Latosol. The experimental design was in randomized blocks, with four replications, in a 5x2x3 factorial scheme, referring to the water salinity levels of 0.5, 1.5, 3.0, 4.5 and 6.0 dS m-1, in soils without and with bovine biofertilizer, and in three evaluation periods: at 90, 120 and 180 days after emergence of the seedlings, in order to evaluate the relative growth rate of the studied morphological parameters, evaluated by the relation of the periods from 90 to 120 and 120 to 180 DAE of the plants in height, stem diameter, root dry matter, dry matter of the aerial part and total (root + aerial part) dry matter. The growth of the neem seedlings was compromised by the degenerative action of the salts of the irrigation water, but with lower severity in those plants of the treatments with the bovine biofertilizer.